A new species of Moelleriella from Yunnan Province in Southwestern China - Wang, Zhi-Qin; Wang, Yao; Wang, Yuan-Bing; Yu, Hong (Phytotaxa, 2022)
We report a new species, Moelleriella puerensis, a fungal pathogen infecting scale insect nymphs, from Puer City, Yunnan Province, Southwestern China. Its diagnostic characteristics include pale yellow and thin pulvinate stromata, ovoid tubercles processes developing on the periphery of the stroma, a fully immersed perithecia, orange ostioles, cylindrical asci, and filiform ascospores disarticulated into short secondary spores. Teleomorph and anamorph typically existed in the same stroma, exclusively anamorphic stromata, with pale yellow conidiomata aggregated in the center of the stroma and several conidiomata per stroma fusing with neighboring conidiomata and existing paraphyses. Morphological observations and phylogenetic analyses of combined nrLSU, rpb1, and tef-1α sequence data confirmed the validity of M. puerensis.